Deformation Zones in Granular Materials in Hoppers During Filling and Emptying Processes - Mróz, Z.; Sielamowicz, I. (Engineering Transactions, 2003)
The present paper is concerned with the simplified analysis of deformation and stress states in converging hoppers during filling and discharge of a granular material. The equilibrium conditions and stress-strain relations are satisfied for cylindrical slice elements assuming dependence of displacement and stress on radial coordinate. The elastic or elasto-plastic material model is used with the Coulomb yield condition and non-associated flow rule. The paper presents a detailed analysis of pressure evolution of a granular material on a hopper wall during the emptying process when the initial active state of pressure is transformed into the passive state. The growth of wall pressure associated with this process is demonstrated. The analytical treatment presented in this paper can be compared with the respective finite element solution.